2020
DOI: 10.3390/su12083393
|View full text |Cite
|
Sign up to set email alerts
|

Business Models Amid Changes in Regulation and Environment: The Case of Finland–Russia

Abstract: Changes in regulation are affecting the international business environment. In this study the impact of regulation changes and ways to benefit from those in Finland and Russia are examined. Logistics and manufacturing companies are studied using the case study approach including ten semi-structured interviews (Finland and Russia) and a survey (Southeast Finland), further supported by an additional survey for logistics sector companies (Southeast Finland). The changes in the business environment have created a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…This information sharing helps build customers' trust in their products and effectively deal with counterfeit and fraud-related issues. Lim et al's (2019) blockchain technology provides a smart contract facility to the supply chain partners, which increased the efficiency of procurement processes and reduce the cost Hoek, 2019;Lähdeaho & Hilmola, 2020). Blockchain shares real-time information with multiple supply chain partners, which control the environmental quality and receive feedback on green product design (Wang et al 2019).…”
Section: Structural Model Assessmentmentioning
confidence: 99%
“…This information sharing helps build customers' trust in their products and effectively deal with counterfeit and fraud-related issues. Lim et al's (2019) blockchain technology provides a smart contract facility to the supply chain partners, which increased the efficiency of procurement processes and reduce the cost Hoek, 2019;Lähdeaho & Hilmola, 2020). Blockchain shares real-time information with multiple supply chain partners, which control the environmental quality and receive feedback on green product design (Wang et al 2019).…”
Section: Structural Model Assessmentmentioning
confidence: 99%
“…BIC (Blockchain-Internet of Things-Cloud) technology layer is an opportunity to upgrade the SYNCHRO-NET system [106]. A study of logistics and manufacturing companies in Finland and Russia found blockchain as an immature technology to base business models upon [107]. Adoption of blockchain technology requires businesses to rethink and redesign the full business model of agriculture and food supply chain, especially in the Covid-19 scenario [108].…”
Section: Industry 40mentioning
confidence: 99%
“…In maritime transport, an increasing focus is placed on the environmental aspect of sustainability because of tightening emission regulations and stakeholder demands. Non-compliance or inactivity related to environmental sustainability can ultimately lead to unexpected costs for companies [16]. With regard to the social aspect of sustainability, safety and security, health, employment, employee engagement, and working conditions should be considered [11,17].…”
Section: Maritime Transport and Sustainabilitymentioning
confidence: 99%